ADDITIONAL NEW RECORD OF EARTHWORMS BELONGING TO FAMILY OCTOCHAETIDAE FROM CHOTANAGPUR PLATEAU REGION OF JHARKHAND - SRIVASTAVA, ROHIT; KUMAR, MANOJ; DANDAPAT, SUKUMAR; RANJAN, RAKESH; SINHA, MANORANJAN PRASAD (The Bioscan, 2023)
Four species of earthworms belonging to family Octochaetidae (Haplotaxida : Oligochaeta) namely Lennogaster pusillus Stephenson, Dichogaster bolaui Gates, Octochaetona surensis Michaelsen, Eutyphoeus waltoni Michaelsen have been collected from different areas of Chhotanagpur plateau of Jharkhand and have been identified and described. Out of the four one species (Dichogaster bolaui) is peregrine while rest three are native species. Two species namely Dichogaster bolaui and Lennogaster pusillus are epigeic while remaining two are endogeic. Occurrence of more native species indicates that the different land use patterns have not affected much the habitat of the earthworms from where they have bbeen sampled.